Influence of organic nutrition on the seed yield and quality in Amaranthus tricolor - SHEEBA REBECCA ISAAC; P. SHALINI PILLAI; DHANYA K. GOPI (Seed Research, 2026)
A field experiment on the seed production in Amaranthus tricolor variety Arun, was conducted in RBD with 12 treatments involving combinations of different sources of nutrients in three replications during December 2009 - March 2010. The results revealed that highest seed yields were recorded in the treatments in which the entire nutrient requirement of the crop was given with organic sources: 100% POP recommendation as organics was highest (607.89 kg ha¹) followed by 150% (517.17 kg ha¹). Economic analysis showed highest benefit cost ratios for inorganic sources despite lower yields on account of the lower cost of nutrient inputs compared to the bulk quantity of organic sources required for the varying levels of substitution. Seed quality characters such as 1000 seed weight and vigour index were also significantly higher for the organically grown seed crop of Amaranthus.